A Rare Case of Male Bullous Lupus Erythematosus Complicated with Subsequent Annular Hypopigmentation - Saori Itoi; Atsushi Tanemura; Chie Tsuji; Shun Kitaba; Akinori Yokomi; Ichiro Katayama; Chiharu Tateishi; Daisuke Tsuruta (Karger Publishers, 2014)
A 57-year-old male had been suffering from an itchy map-shaped symmetrical erosive erythema with a crust that was attached to his upper arm and buttock, and occasionally he suffered from spiking fever. Laboratory examinations showed neither anti-desmoglein 1/3 antibodies nor anti-BP 180 antibodies, and he fulfilled the criteria for a diagnosis of systemic lupus erythematosus (SLE). Histologically, there was eosinophilic necrosis of keratinocytes, liquefaction and degradation with severe lymphocyte infiltration into the epidermis and subepidermal blister formation, suggestive of a variant of SLE, bullous lupus erythematosus (BLE). One month after remission of BLE, peculiar annular hypopigmentation appeared on the peripheral borders. An immunohistochemical analysis showed a decrease in Melan A-positive melanocytes and concomitant pigment incontinentia, with dense infiltration of CD8+ T cells and IL-17A+ Th17 cells. An ultrastructural analysis revealed a decrease, but not a complete disappearance, of both melanocytes and melanosomes, and no impairment in melanosomal transfer. In this case report, we would like to introduce the development of annular depigmentation complicated with BLE, and discuss the effects of lupus condition on melanocyte damage based on immunohistological and electromicroscopic findings of those vitiliginous lesions.